2016
DOI: 10.1186/s12906-016-1259-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of aqueous extract and bioactive compounds identified from the fruits of Hancornia speciosa Gomes (Apocynaceae)

Abstract: BackgroundHancornia speciosa Gomes (Apocynaceae), popularly known as “mangabeira,” has been used in folk medicine to treat inflammatory disorders, hypertension, dermatitis, diabetes, liver diseases and gastric disorders. Although the ethnobotany indicates that its fruits can be used for the treatment of ulcers and inflammatory disorders, only few studies have been conducted to prove such biological activities. This study investigated the anti-inflammatory properties of the aqueous extract of the fruits of H. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 48 publications
0
33
0
2
Order By: Relevance
“…Similar to the chemical composition of the leaves shown herein, the aqueous fruit extract of the same species showed the phenolics rutin and chlorogenic acid as prominent constituents. The fruit extract and the trunk latex exhibited anti-inflammatory activity in animal models [ 36 , 37 ]. Additionally, the latex showed significant angiogenic activity and a potential osteogenic effect, and had no cytotoxic or genotoxic effects on life systems [ 19 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the chemical composition of the leaves shown herein, the aqueous fruit extract of the same species showed the phenolics rutin and chlorogenic acid as prominent constituents. The fruit extract and the trunk latex exhibited anti-inflammatory activity in animal models [ 36 , 37 ]. Additionally, the latex showed significant angiogenic activity and a potential osteogenic effect, and had no cytotoxic or genotoxic effects on life systems [ 19 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the authors showed for the first time that HEVP and EAEVP have topical anti-inflammatory effect, which is possibly related to the presence of secondary compounds, since some flavonoids (rutin, luteolin, and apigenin) were identified in EAEVP and this effect may involve different mechanisms in the cutaneous inflammation [28,29]. Rutin, for example, inhibited the xilol-induced ear edema and reduced the cell migration and the levels of cytokines were also observed [30], while luteolin exhibits anti-inflammatory effects by blocking the activity of heat shock protein 90 in macrophages [31]. In addition, apigenin has been effective against the LPS-induced acute lung injury due to its ability of primary inhibition of cyclooxygenase-2 (COX-2) gene expression and nuclear factor kB (NF-kB) gene expression and the protective mechanism of apigenin may be attributed partly to decreased production of proinflammatory cytokines [32].…”
Section: Discussionmentioning
confidence: 99%
“…Only recently the fruits of H. speciosa have been investigated for their potential pharmacological activity. Rutin and chlorogenic acid were the bioactive constituents isolated from an aqueous extract of the fruits that showed a role in controlling inflammatory events [10]. The fruit pulp, in which phenolic compounds such as gallic acid, catechin, chlorogenic acid, vanillic acid, o-coumaric acid, rosmarinic acid, and rutin were identified, has shown an antimutagenic effect [11].…”
Section: Bmcmentioning
confidence: 99%
“…To date, only a few studies have investigated the potential therapeutic properties of H. speciosa fruits. A recent publication showed that rutin and chlorogenic acid, isolated from the aqueous extract of the fruits, were able to decrease edema and cell migration in different models of inflammation, and also reduce the levels of proinflammatory cytokines such as IL-1β, IL-6, IL-12, and TNF-α [10]. Another study showed that mangaba pulp has a potential antimutagenic effect [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation